Islamic Law Analysis of Divorce Intervened by Parents (Case Study in Jatirogo Village, Bonang Subdistrict, Demak District) - Khoridatul Himmah; Inna Faizatal Ngazizah (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
A husband's economic condition becomes a problem in a child's family. Parental intervention is a natural thing, but in a child's household, let the child live independently and learn to manage problems in the household. However, what if parental intervention results in divorce when the problems in the household can actually be resolved well. This happened in Jatirogo Village, Bonang District, Demak Regency. Some married couples divorce due to parental intervention. The aim of this research is to describe the forms of parental intervention towards children's families which result in divorce, the factors of divorce caused by parental intervention towards married couples, and to describe the views of Islamic law regarding forms of parental intervention in divorce towards children's families. This researcher used qualitative methods, with a type of field research, data collection process, interview method with 3 informants who were directly interviewed in a structured manner. This research was conducted for 2 months. The results of the research show that the factors that influence parents to intervene in divorce in Jatirogo Village, Bonang District, Demak Regency are: The presence of parental intervention factors has several impacts on the family and household on children, including the very different parenting patterns of mothers and fathers, changes in thinking patterns and character in children, the presence of traumatised attitudes and mental weakness. Apart from that, this research shows that the analysis of Islamic law intervened in parental divorce in Jatirogo Village, Bonang District, Demak Regency. Based on research results, this form of parental intervention is not prohibited in Islamic law, however, if it causes bad impacts such as divorce experienced by husband and wife households.